Characterization of the Arabidopsis thaliana 2-Cys peroxiredoxin interactome. (November 2016) - Cerveau, Delphine; Kraut, Alexandra; Stotz, Henrik U.; Mueller, Martin J.; Couté, Yohann; Rey, Pascal
Highlights: The signaling functions of plant 2-Cys peroxiredoxins remain elusive. 2-Cys PRX partners have been isolated using a non-targeted approach. More than 65 potential plastidial partners have been identified in leaf extracts. The approach is validated by the presence of known 2-Cys PRX partners. The data provide perspectives for characterizing plant 2-Cys PRX functions. Abstract: Peroxiredoxins are ubiquitous thiol-dependent peroxidases for which chaperone and signaling roles have been reported in various types of organisms in recent years. In plants, the peroxidase function of the two typical plastidial 2-Cys peroxiredoxins (2-Cys PRX A and B) has been highlighted while the other functions, particularly in ROS-dependent signaling pathways, are still elusive notably due to the lack of knowledge of interacting partners. Using an ex vivo approach based on co-immunoprecipitation of leaf extracts from Arabidopsis thaliana wild-type and mutant plants lacking 2-Cys PRX expression followed by mass spectrometry-based proteomics, 158 proteins were found associated with 2-Cys PRXs. Already known partners like thioredoxin-related electron donors (Chloroplastic Drought-induced Stress Protein of 32 kDa, Atypical Cysteine Histidine-rich Thioredoxin 2) and enzymes involved in chlorophyll synthesis (Protochlorophyllide OxidoReductase B) or carbon metabolism (Fructose-1, 6-BisPhosphatase) were identified, validating the relevance of the approach. Bioinformatic and bibliographic analyses allowed the functional classification of the identified proteins and revealed that more than 40% are localized in plastids. The possible roles of plant 2-Cys PRXs in redox signaling pathways are discussed in relation with the functions of the potential partners notably those involved in redox homeostasis, carbon and amino acid metabolisms as well as chlorophyll biosynthesis.